PERANCANGAN ANIMATED MUSIC VIDEO UNTUK LAGU KELAPA MUDA BAND - Yesaya Sabda Imanuel; Ahmad Khoirul Anwar; Yudi Wibowo (Canthing, 2024)
Kelapa Muda Band is an experimental jazz music group originating from Lampung, Indonesia, and has won the first championship in one of the international jazz music competitions. However, the Kelapa Muda Band is still rarely recognized by the general public who are not concerned with the jazz music genre. One problem is the lack of promotional media for music video clips. Therefore, promotional media for music video clips is needed to increase the name of the Kelapa Muda Band, especially the song "Pagi dan Hujan". The design was made to promote the song "Pagi dan Hujan" from Kelapa Muda Band as an attractive promotional medium. It method starts from Development, pre-production, production, post-production, and distribution. Therefore, the design can produce music video clips and some of merchandise that are interesting in terms of concept and visualization. Keywords: Video Clip, Animation, Jazz